MULTIVARIATE ANALYSIS OF VARIANCE (MANOVA) DALAM MOTIVASI WANITA BEKERJA (STUDIKASUS DIKOTA SURAKARTA) - Siti Aisyah Tri Rahayu (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
The aims of this paper are: 1) To measures the differences between two dependent variables of woman's motivation on work is caused by economic and education factor; 2) To explain the interaction effect between independent variable age and culture to women's work motivation caused by economic and education factor.The empirical result of this research with MANOVA models are as follows. The impact of self-actualization, culture, husband's income, family's income on women determination of labor force participation has been very significant. Husband' income and culture have a significant negative effect on women determination of labor force participation. While self-actualization and family's income, have a significant positive effect on women determination of labor force participation.Based on the result, there are differences between independent variables (age and culture) vector mean to dependent variables (economic and education motivation)All multivariate tests indicate that the interaction effect is significant. Both Variables culture and education have a significant effect income variable at 0,05 significant level but not significant on education variables.One of the crucial policy implications of this paper is that we must enhance the government policy on that base on that result. Differences between male and female wages in the same working still exist now. Base on that reality, we must enhance the government policy to protection women's right on the economic activity and the equality in the human right both male and female worker.